Linkage data on two new swine-requiring mutants, one of which is a new locus, serine-5 (ser-5) - J. B. Maxwell; F. Kline; R. S. Bengtson (Fungal Genetics Reports, 1974)
Linkage data on new ser mutants; new locus, ser-5